The importance of industrial linkages for the enterprises' innovation activity in Małopolska region 2008-2010 = Znaczenie powiązań przemysłowych dla aktywności innowacyjnej przedsiębiorstw w regionie małopolskim w latach 2008-2010 - Świadek, Arkadiusz; Szopik-Depczyńska, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The main objective of the study was an attempt to search for the conditions affect the nature of supply chains for enterprises innovative activity within the regional industrial systems, and consequently determine the frame conditions for the model of regional innovation networks, taking into account the specificities of Małopolskie region. The study was based on a questionnaire on a group of 500 companies from Małopolska. The study used probity modeling. This method is an effective research tool for large, but the static tests in which the dependent variable has a qualitative character.
Keywords: innowacja; region; łańcuch dostaw; przemysł; innovation; supply chain; industry